Salt soluble without jelly-like component from the oviducal gland induces chorionic expansion in the ova of the Japanese common squid Todarodes pacificus. Issue 4 (1st October 2016) - Adachi, Kohsuke; Yabumoto, Mao; Yoo, Haekyun; Morioka, Katsuji; Ikeda, Yuzuru; Ueta, Yukio; Sakurai, Yasunori
Abstract: In vitro fertilization of squid requires the jelly substance found in the female oviducal gland; yet, the active component of this substance that facilitates fertilization remains unknown. Here, we used biochemical methods to separate the jelly substance of Todarodes pacificus (Oegopsida) and Sepioteuthis lessoniana (Myopsida family) into four fractions; specifically, two water soluble fractions (Molecular weight > 10, 000 and < 10, 000), one salt soluble fraction, and one insoluble fraction. The salt soluble fraction of T. pacificus induced chorionic expansion (perivitelline space formation), which precedes the normal embryonic development of ova. In contrast, the salt soluble fraction of S. lessoniana elicited insufficient expansion of the ova, only producing embryos with high abnormality rates. These results suggest that the salt soluble component(s) (not the jelly-like substances) in the oviducal gland induce chorionic expansion and hatching in Oegopsida, and that these components may be similar in Myopsida.